Performance Audit of National Rural Health Mission (NRHM) in Maharashtra - CAG of India (CAG of India, 2010)
This performance audit reveals that even after four years of its launch in April 2005 and a mammoth spending of Rs 1130 crore, the Government of India sponsored National Rural Health Mission programme in Maharashtra has still not been able to come out of its initial hurdles, such as lack of reliable beneficiary database, improper planning etc. The performance audit noted serious gaps in the delivery of mission objectives. Although the mission made considerable progress in achieving Revised National Tuberculosis Control Programme, Infant Mortality Rate and Total Fertility Ratio targets, these were overshadowed by suboptimal use of the available health care infrastructure such as mobile medical units. The Mission needs to seriously introspect into the functioning of the Rugna Kalyan Samitis besides upgrading the standards of PHCs and Sub-centres to the level of Indian Public Health Standards.
For the Period 2005-06 to 2008-09